Collective Defense Strategies: tactics to mitigate suffering in nurse’s hospital work - Élissa Jôse E. R. Cruz; Norma Valéria Dantas de Oliveira Souza; Márcia Tereza Luz Lisboa (Online Brazilian Journal of Nursing, 2007)
Introduction: Qualitative, descriptive study that had as object the defense collective strategies made by assistance nurses in order to mitigate the suffering that comes from hospital work organization. Objective: To characterize the defense collective strategies made by nurses at medical and surgical clinics context. Methodology: The study scenario was a University Hospital, the individuals were 25 nurses and the data collection techniques were: semi-structured interview and observation. The analysis method was based in the hermeneutic-dialectic that has showed the following categories: defensive strategies made by assistance nurse collective. Main Results: The analysis showed twelve defense collective strategies that the nurse use to mitigate and/or occult the suffering came from work organization. Conclusions: It was stated that the referred strategies can be interesting tactics against the suffering since they allow the nurse to keep on working without getting physically and psychologically sick, it means, to resist working organization pressures without experiencing classic pathologic processes. Thus, they can be characterized as a factor that results in alienation, hiding the real comprehension of work context.